Hubungan Peran Ayah Dengan Penyesuaian Diri Mahasiswa Baru Fakultas Ilmu Sosial Universitas Islam Negeri Sumatera Utara - Pulungan, Akmaliyah Hakiki; Dewi, Salamiah Sari (Jouska: Jurnal Ilmiah Psikologi, 2024)
This study aims to investigate the relationship between fatherhood and self-adjustment in new students of the Faculty of Social Sciences, State Islamic University of North Sumatra. Self-adjustment is defined as an individual's ability to cope with discomfort and exhibit behavior acceptable to the environment. This research method is quantitative with a population of 125 new students from the communication science study program. Sampling is carried out in total sampling. Data were collected through the fatherhood scale and self-adjustment scale, then analyzed using the Pearson product moment correlation. The results showed a correlation coefficient of 0.478 (P 0.05), indicating a significant positive relationship between fatherhood and self-adjustment. The coefficient of determination (r2) of 0.229 indicates that 22.9% of the variation in self-adjustment can be explained by the role of the father. The findings showed that paternity and self-adjustment were very low, with significant differences between the empirical mean and the hypothetical mean. Therefore, the proposed hypothesis is declared acceptable.